Plasma Cardiac Troponin-I Concentration in Normal Horses and in Horses with Cardiac Abnormalities - Jonathan H. Foreman; Brett S. Tennent-Brown; Mark A. Oyama; D. David Sisson (Animals)
Cardiac troponin-I (cTnI) is a highly sensitive and specific marker of myocardial injury detectable in plasma by immunoassay techniques. Inclusion criteria over a 3-year period required a diagnosis of cardiac disease accompanied by electrocardiographic (ECG) and cardiac ultrasound examinations (n = 23) in adult horses (≥2 years of age). A second group of normal adult ponies (n = 12) was studied as a reference group. Heparinized jugular venous blood samples were collected and centrifuged within 30 min, and the plasma was separated and frozen at −70 °C for subsequent batched cTnI analysis. The lower limit of detection was 0.01 ng/mL, and the upper limit was 100 ng/mL of plasma. Normal equine plasma cTnI concentrations ranged from 0.01 to 0.03 ng/mL (n = 12). Horses with non-arrhythmogenic murmurs (n = 4) included tricuspid (0.05 ng/mL cTnI), mitral (0.07), and aortic insufficiencies (0.01, 0.02). Horses with benign atrial fibrillation (n = 8) had a cTnI range of <0.01–0.09 ng/mL, with four horses having cTnI concentrations falling slightly outside the reference range (0.04, 0.05, 0.06, and 0.09). Horses with ventricular arrhythmias (ventricular premature contractions or ventricular tachycardia) and documentable myocardial toxicities or immunological reactions (n = 5) had cTnI concentrations of 0.05, 0.21, 0.31, 15.18, and >100 ng/mL. Horses with ventricular arrhythmias but no documentation of myocardial toxicity (n = 3) had cTnI concentrations of 0.34, 0.46, and 80.42 ng/mL. When grouped by arrhythmia type and compared using the Mann–Whitney Rank Sum Test, the median ventricular arrhythmia cTnI (0.40 ng/mL) was significantly higher than the median atrial fibrillation cTnI (0.04 ng/mL, p < 0.001). It was concluded that horses with myocardial toxicities and ventricular arrhythmias often had severe elevations in plasma cTnI.